“A View of Ineffable Charm…” The Black Sea in the Ukrainian Prose of the Late 19th Century - Boiko, Nadia (Poznańskie Studia Slawistyczne, 2024)
The article analyses the image of the Black Sea in the prose works of Ukrainian writers of the last two decades of the 19th century. The sea is an important component of their creative biographies and a source of inspiration. It is also a part of their characters’ inner world symbolizing the freedom and passionate love, saving them from their loneliness and routine. The research demonstrates the philosophical components of the sea complex in the analyzed works of fiction, outlines their main motifs and psychological details. It specifies the authors’ contributions to the artistic representation of the Black Sea (the representational and informative descriptions vs the expressive descriptions) and its conceptualization as a space associated with Ukraine.